Mendelian randomization analysis reveals genetic evidence for a causal link between inflammatory bowel disease and uterine cervical neoplasms - Cao, Chunge; Sun, Xiaorui; Chen, Xiaohu; Zhang, Ying; Yue, Chaoyan (Frontiers in Genetics, 2025)
BackgroundInflammatory bowel disease (IBD) has been reported to be associated with risk of uterine cervical neoplasm. We aimed to evaluate the causal relationship between IBD and uterine cervical neoplasm using a bidirectional Mendelian randomization analysis.MethodsWe derived instrumental variables for IBD, including Crohn’s disease and ulcerative colitis, from the IEU Open genome-wide association study (GWAS) database, and for the histological subtypes of uterine cervical neoplasm from the FinnGen repository’s GWAS data. The collected GWAS data predominantly represent individuals of European ancestry. The inverse-variance weighted (IVW) method was employed as primary analysis approach.ResultsIBD (IVW odds ratio = 1.127, 95% confidence interval = 1.016–1.251; p = 0.024) and CD (IVW odds ratio = 1.119, 95% confidence interval = 1.023–1.224; p = 0.014) exhibited a significant causal effect on malignant cervical carcinoma. Sensitivity analyses confirmed these findings.ConclusionGenetically predicted IBD and CD are risk factors for the development of malignant cervical carcinoma. Patients with IBD and CD require specific attention to prevent cervical squamous cell carcinoma. Further studies to elucidate the underlying mechanisms may reveal new therapeutic targets.